(3GdcfR GdCaNQ hGdSQ GdCYXe aj JUQja GdMLQ GdecQes - (3CHh GdbGSe eMeO Hf CMeO GdSeGhi GdYQGbi,J (B580 (3g` s
(3ChdgG (B:s
(3CeG HYO aMbjb Ydjce jG eYTQ GdeJThbjf Edi ZGjI GdfLGI Cf JJYQahG SHjdgG Ef cfJe UGObjf s
(3BNQgG (B:s
(3JeJ GdQSGdI GdeSeGI HGdcfR GdCaNQ hGdSQ GdCYXe ai JYQja GdMLQ decQe ef JCdja GdSeGhi GdYQGbi QMeg Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B81s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B496 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B177 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs